The status of Iraq in the Middle East - visions and dimensions (Journal of the College of Basic Education, 2023)
The research deals with one of the contemporary and important issues; Which has deep roots in political historyFor the major countries, Iraq has a direct impact on the course of political transformations in the Middle East, pIt is the heart of the Greater Middle East project; The transformations taking place in the region and the world as a whole will not happenAway from his expected and decreed role within the international contexts that define the political features of the outside world;Despite what has been written on the subject, it needs a lot of explanation and explanation, because it is covered in more than one articleA formula that corresponds to the international, regional and even local data of the relevant country, and in this matterWe note that Iraq as a country has become the link that brings together all the disparate international trends. to meet onhis land in order to draw future plans; And if the Greater Middle East project is one of the plansTo control the future in the region, this means the presence of players who play their specific roles for them; on meThat its results are in the supreme interest of a country like the United States of America} and whose role appearsMarbinta to the extent of the stability of the situation in Iraq; If this becomes the case, then this means the status of the statesUSA is on the right track in building the project; And laying the brunt of carrying it out for the restinternational and regional parties; What is required of us at the current stage is an extensive reading to understand the dimensions of thisThe project, its objectives, and what will happen to Iraq and the Middle East region as a result of its implementation; and try to study itObjectively and impartially away from the narrow frameworks that will determine our concept of international politics and its toolsOn this basis, our research came to provide a brief idea of what is happening within the concept of the Middle East projectAl-Kabeer and Iraq's political connection to this project.